THE RELATIONSHIP KNOWLEDGE AND OBEDIENCE DIET WITH BLOOD SUGAR LEVELS IN PATIENTS WITH TYPE II DIABETES MELLITUS IN THE DEPARTAMENT SURGICAL AND OUT PATIENT CONSULTATION, HNGV, DILI, TIMOR-LESTE 2023 - Manuela Alves, Maria; Pereira, Natalia; Jose Soares Tilman, Etelvina; Carvalho de Araújo, Eugenia; Barreto, Meriana; Deonisio Ximenes, Jose (CV RIFAINSTITUT, 2024)
According to the IDF in 2017 stated that the number of DM in 2017 reached 425 million people, for adults ranging from ages 20-79 (IDF, 2017) in 2019 the prevalence of DM cases in the world continues to increase to reach 436 million people in the world (IDF, 2019) global DM prevalence in 2021 will reach 536 million with a total mortality of 6.7 million people (OMS, 2021). East Timor population 1,5 % suffers from the disease diabetes mellitus, based on the result of the national survey that was implemented by the Ministry of Health with UNTL in 2014 on the risk of non-infected diseases in East Timor. MdS (2015). Agreement on the last date that WHO published in relation to service with MdS in 2020 mortality rate of diabetes mellitus in East Timor reaches number 156 or 2,21 % with total mortality 22.46 % 100.000 inhabitants klasifika East Timor occupies number 104 in the World (WHO & MdS 2020). To identify the relationship between level of knowledge and obedience with diet against glucose level to the patient with DM type II in the Departament Surgical and Outpatient Consultation, HNGV, Dili, of 2023 year. The research desing uses quantitative corelational analytical study type with its cross sectional. Based on the result analyzes test statistics Spearman Rank P value 0,000 demonstrates that value is less than 0,05 means that there is a relationship between knowledge with blood glucose level and result with correlation value r = 0,539 which located between 0,50-0,74 category to strong correlation. And the relationship between obedience, diet and blood glucose level, the result analyzes a statitical test that uses Spearman Rank P value 0,000, which shows that a value of 0,000 is less than 0,05 and a result with a correlation value of r=0,785, which is located between 0,75-0,99 category is the strongest correlation. This survey sample has a positive and significant relationship between knowledge and obedience to diet agaist blood glucose level with DM type II in the Department of Surgery and External Consultation and Ambulatory HNGV,Dili,year 2023.